Comparison of microbubble presence in the right heart during mechanochemical and radiofrequency ablation for varicose veins. (July 2017) - Moon, KH; Dharmarajah, B; Bootun, R; Lim, CS; Lane, TRA; Moore, HM; Sritharan, K; Davies, AH
Objective: Mechanochemical ablation is a novel technique for ablation of varicose veins utilising a rotating catheter and liquid sclerosant. Mechanochemical ablation and radiofrequency ablation have no reported neurological side-effect but the rotating mechanism of mechanochemical ablation may produce microbubbles. Air emboli have been implicated as a cause of cerebrovascular events during ultrasound-guided foam sclerotherapy and microbubbles in the heart during ultrasound-guided foam sclerotherapy have been demonstrated. This study investigated the presence of microbubbles in the right heart during varicose vein ablation by mechanochemical abaltion and radiofrequency abaltion. Methods: Patients undergoing great saphenous vein ablation by mechanochemical abaltion or radiofrequency ablation were recruited. During the ablative procedure, the presence of microbubbles was assessed using transthoracic echocardiogram. Offline blinded image quantification was performed using International Consensus Criteria grading guidelines. Results: From 32 recruited patients, 28 data sets were analysed. Eleven underwent mechanochemical abaltion and 17 underwent radiofrequency abaltion. There were no neurological complications. In total, 39% (11/28) of patients had grade 1 or 2 microbubbles detected. Thirty-six percent (4/11) of mechanochemical abaltion patients and 29% (5/17) of radiofrequency ablation patients had microbubbles with no significant difference between the groups ( p =0.8065). Conclusion: A comparable prevalence of microbubbles between mechanochemical abaltion and radiofrequency ablation both of which are lower than that previously reported for ultrasound-guided foam sclerotherapy suggests that mechanochemical abaltion may not confer the same risk of neurological events as ultrasound-guided foam sclerotherapy for treatment of varicose veins.